2012
DOI: 10.1021/jp306545v
|View full text |Cite
|
Sign up to set email alerts
|

Are 4-Mercaptobenzoic Acid Self Assembled Monolayers on Au(111) a Suitable System to Test Adatom Models?

Abstract: The adsorption of 4-mercaptobenzoic acid (MBA) has been studied on Au(111) by scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy (XPS), electrochemical techniques, and density functional theory (DFT) calculations. Results show that MBA molecules adsorb on the Au surface via a thiolate bond, arranged in a (√3×4) lattice with coverage θRS = 0.25. DFT data show the strong effect of aromatic ring interactions in stabilizing the adsorbed molecules. The total absence of vacancy islands upon thiol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 40 publications
4
49
1
Order By: Relevance
“…The distances, sizes and corrugations in our measurements indicate that MBA molecules adsorb in a nearly planar orientation on Au(110), contrary to what has been reported for other surfaces. [46][47][48][49][50] Further details of the molecular structure are resolved in constant height measurements of the tunneling current and the frequency shift. The tunneling-current map ( Fig.…”
mentioning
confidence: 99%
“…The distances, sizes and corrugations in our measurements indicate that MBA molecules adsorb in a nearly planar orientation on Au(110), contrary to what has been reported for other surfaces. [46][47][48][49][50] Further details of the molecular structure are resolved in constant height measurements of the tunneling current and the frequency shift. The tunneling-current map ( Fig.…”
mentioning
confidence: 99%
“…[a] M. C. Rodríguez Gonzµlez (4-MBA)S AMs on Au(111)b yu sing different techniques. [15,16] Our results showed that this molecule initially forms ordered domainsw ith a( 4 p 3) lattice with two molecules per unit cell and surface coverage q = 0.25 and then undergoes ap hase transition to reach q = 0.33, which is av alue consistentw ith the c(4 2) lattice. [16] On the other hand, 4-MBA adsorbs on the Au(110) from the gaseous phase forming dimerics tructures that are nearly parallel to the Au surface, forming a( 5 4) lattice with q = 0.20.…”
Section: Introductionmentioning
confidence: 58%
“…Similar STM images taken on 4-MBA covered substrates showl arger domains, which can reach 50 nm in size (Figure 1f), consisting of molecular rows separated by 0.69 AE 0.02 nm. [15,16,18] To estimate the surfacec overage of the 2-MBA on the Au(111), surface reductived esorption measurements were performed. [15,16,18] To estimate the surfacec overage of the 2-MBA on the Au(111), surface reductived esorption measurements were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8] The failure of small aromatic thiols to form staple moieties has been explained considering their lower coverage and adsorption energy compared to alkanethiols (they do not compensate the energy cost to extract the Au atoms from the terraces). 9 Similar arguments 4 have been used to explain the absence of staples when 6-mercaptopurine (6MP, Figure 1), a small aromatic thiol of relevance for the treatment of some leukemias and autoimmune conditions because of its role as purine antagonist 10 , is adsorbed on the Au(111) 7 and Au(001)-(1×1) surfaces. 11 However, there is also another possible reason for this behavior: a low chemical affinity of the aromatic molecules to the Au adatoms, a fact that could also explain the formation of Au islands rather than vacancy Au islands.…”
Section: Introductionmentioning
confidence: 75%